(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Whale shark occurrence in Probolinggo differs from other Indonesian locales, suggesting a link to zooplankton availability. Zooplankton composition and whale shark emergence are the focus of this study. From December 2017 to November 2018, six observation points were made each month. A plankton net filters and lugol preserves water. Olympus CX23 microscope observations were repeated twice. The spatial analysis revealed varying whale shark numbers at each station (Chi-square test, X2 = 1418.6, P <0.05), with six sharks observed at station PR_5. Zooplankton numbers were similar at each location. Temporal analysis revealed significant differences in whale shark appearance each month (Chi-square test, X2 = 81.04, P <0.05), with March and November having the highest appearance among the three individuals. The amount of zooplankton varied (Chi-square test, X2 = 148.61, P <0.05), with the highest abundance in April and March. Whale shark appearance and zooplankton composition were not correlated (r = 0.01, P< 0.05) both geographically and temporally. Whale sharks were linked to zooplankton kinds. Results indicate whale sharks are particularly interested in Acartia sp. (r = 0.3, P < 0.05). This suggests that whale sharks’ appearance is determined by their demand for food, not zooplankton availability.